State Violence in Indonesian Conservation Area Conflict Management: Perspectives from The Media - M. Danang Anggoro; San Afri Awang; Purwo Santoso; Lies Rahayu Wijayanti Faida (Jurnal Ilmu Kehutanan)
The imposition of conservation areas by the state through violence caused prolonged conflict in the management of conservation areas in Indonesia. Therefore, the need to understand and manage conflict as a holistic process guides this research, in which the goal is to better understand the dimensions of state violence. This research complements previous studies that are more focused on superficial symptoms, which have not fully been able to uncover the invisible levelsthat make up the dimensions of violence.This study uses online media, namely Kompas Online, which represents the general media, as well as Mongabay, which represents environmental media, including news related to conflicts in conservation areas for the period of 2011 - 2017. State violence in the news is described in the dimensions of violence using content analysis. The content analysis is carried out in this study and follows a framework for simplified content analysis from Krippendorf (2004) and Istania (2010) with the aim of conducting descriptive content analysis intended to describe a particular message or text (Rossy and Wahid, 2015), which is focused on the dimensions of state violence in the management of conservation areas.The dimensions of state violence can be fairly intact through the perspective of news in the mass media. This is helpful for better understanding conflicts that involve relations between the state and local communities due to the control of the management of conservation areas as a natural resource. To address the conflict, support is needed to find the identity of conservation area management through a cultural approach so as to build optimism that conflicts in the management of conservation areas can be handled properly.